Practice tools for screening and monitoring insomnia in children and adolescents with autism spectrum disorder - Banaschewski, Tobias; Bruni, Oliviero; Fuentes, Joaquin; Hill, Catherine Mary; Hvolby, Allan; Posserud, Maj-Britt; Schroder, Carmen (Journal of autism and developmental disorders, 2022)
Between 50-80% of children with autism spectrum disorder (ASD) have insomnia, which adversely affects their mental and physical health. However, there is no consensus to-date on suitable tools for insomnia screening and monitoring in daily clinical practice. An expert panel of child neuropsychiatry and sleep specialists, with expertise in children with neurodevelopmental disabilities, recommends: (1) performing insomnia screening of all children with ASD; (2) considering discussion or referral to a sleep specialist when comorbid sleep disorders are suspected. The panel further developed structured, brief screening and monitoring tools to facilitate insomnia screening and management in daily practice, monitor treatment effectiveness and standardize and compare outcomes across clinical settings to improve care and well-being of children with ASD and their families.